2006
DOI: 10.1111/j.1469-0691.2005.01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of non-multiresistant methicillin-resistant Staphylococcus aureus (including EMRSA-15) in Kuwait Hospitals

Abstract: This study characterised non-multiresistant methicillin-resistant Staphylococcus aureus (nmMRSA) isolates from Kuwait hospitals to ascertain whether they were community-acquired MRSA (CA-MRSA). Forty-two nmMRSA isolates obtained between July 2001 and October 2003 were analysed by staphylococcal cassette chromosome mec (SCCmec) typing, bacteriophage typing, production of Panton-Valentine leukocidin (PVL), urease and staphylococcal enterotoxins A, B, C and D, TSST-1, and by pulsed-field gel electrophoresis (PFGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 42 publications
1
48
0
Order By: Relevance
“…The results of this comparison confirmed that the UAMS isolates are closely related to each other and to (Cassat et al, 2005), which is a prominent clinical isolate found in diverse geographical areas worldwide (Aires de Sousa et al, 2005;Johnson et al, 2005;Nimmo et al, 2006;Udo et al, 2006). Our analysis also confirmed that the cluster containing UAMS-1, UAMS-601 and EMRSA-16 is the most distantly related, among the strains we examined, to the prototype laboratory strains NCTC 8325 and RN6390 (Cassat et al, 2005).…”
Section: Introductionsupporting
confidence: 73%
“…The results of this comparison confirmed that the UAMS isolates are closely related to each other and to (Cassat et al, 2005), which is a prominent clinical isolate found in diverse geographical areas worldwide (Aires de Sousa et al, 2005;Johnson et al, 2005;Nimmo et al, 2006;Udo et al, 2006). Our analysis also confirmed that the cluster containing UAMS-1, UAMS-601 and EMRSA-16 is the most distantly related, among the strains we examined, to the prototype laboratory strains NCTC 8325 and RN6390 (Cassat et al, 2005).…”
Section: Introductionsupporting
confidence: 73%
“…The EMRSA-15 clone is one of the pandemic MRSA clones (18) and has been identified in several countries such as The Netherlands (18,62), Denmark (21), Germany (63), Ireland and Sweden (18), the Czech Republic (32, 33), Australia and New Zealand (23,46), Kuwait (59), and Spain (6,35,47).…”
Section: Discussionmentioning
confidence: 99%
“…CAMRSA strains are characterized by their susceptibility to a wide range of non-beta-lactam antibiotics, low methicillin MICs, and the carriage of the type IV or V staphylococcal cassette chromosome mec (SCCmec) element. In contrast health care-associated MRSA strains are usually multiresistant to non-beta-lactam antibiotics and contain type I, II, or III SCCmec elements (1,13).…”
mentioning
confidence: 99%
“…CAMRSA isolates obtained in Kuwait hospitals were previously characterized by antibiotic resistance patterns and SCCmec typing (13), but their sequence types were not determined. Consequently, it was not possible to ascertain whether the CAMRSA strains isolated in Kuwait hospitals constituted indigenous or imported internationally recognized clones.…”
mentioning
confidence: 99%
See 1 more Smart Citation